The Impact of COVID-19 Cases on Stock Prices of Selected Companies Representing Tourism and Banking Sectors - Dayan, Volkan; Bolek, Monika; Trinidad-Segovia, Juan E. (Journal of Finance and Financial Law, 2023)
The purpose of the article/hypothesis: The purpose of the article is to analyse the relationship between stock prices of selected companies and COVID-19 cases in those countries where the tourism and banking sectors have a high share of national income, such as Croatia, Italy and Spain. Methodology: The methods used are Breakpoint Unit Root Tests to determine whether a time series is stationary or not, and ARDL cointegration technique for cointegration testing. Results of the research: It was found that the number of COVID-19 cases negatively impacted the tourism and banking market in surveyed EU countries.